IMPLEMENTATION OF PROBLEM BASED LEARNING METHOD IN COMPETENCY BASED CURRICULA WITH STUDENT’S SOFTSKILL IN PSIK UR - Ari Pristiana Dewi; Febriana Sabrian; Erwin Erwin (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction. Improving the quality of education makes a shift in educational paradigm in Indonesia. Conventional teacher-centered curricula is changing to competency-based curricula (CBC) with focus on student-centered learning. The purpose of this study was to identify relationship between the implementation of Problem-Based Learning (PBL) method in CBC with students’ soft skills. Method. The study design was cross sectional correlation with 97 respondents as the sample. Analysis of the data using univariate and bivariate analysis with the test used was the chi square test. Results. The results of the study showed that there was no relationship in the implementation of PBL method in CBC with students’ soft skills (ρ = 0.646). Discussion. Based on the results, this study suggested to the academic head officer of PSIK UR to be able to evaluate periodically the implementation of CBC in order to achieve quality learning to produce students who can perform both hard skills and soft skills. Keywords: CBC, PBL, softskills, student